IMPROVING STUDENTS LANGUAGE PROFICIENCY THROUGH ACTIVE LEARNING STRATEGIES ACROSS LEARNING STYLE - Etika Ariyani (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2019)
Abstract:  This study aims to investigate that active learning strategies can improve the students language proficiency in the second year of SMAN 1 Kediri, West Lombok, West Nusa Tenggara. the subjects of this study were consisted of 31 students. The method used in this study was Classroom Action Research, the design applied in this study was a collaborative action research. This research carried in two cycles, each cycle consisted of two meetings, the data  were gathered  through interview, field notes, questionnaire and test. The result of this study showed that there was improvement  of students language proficiency. Most of students gained good scores gradually at the end of each cycle. The score of Minimum Mastery Criterion  of English lesson was 70. The students  mean score in preliminary study was 55.85. the mean score  in the first cycle was 66.13. the mean score in the second cycle was 73.19. in addition, there was  a positive  response from the English teacher about implementing the action and changes of students learning styles. In conclusion, using active learning strategies could improve students language proficiency across their learning styles.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penerapan active learning strategies dapat meningkatkan kemampuan berbahasa inggris bagi siswa SMAN 1 Kediri, Lombok Barat, Nusa Tenggara Barat. Populasi penelitian sebanyak 31 siswa. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas dengan rancangan kolaboratif. Penelitian tindakan kelas ini terdiri atas dua siklus, setiap siklus terdiri atas dua kali pertemuan, data dikumpulkan melalui interview, catatan lapangan, kuisioner dan test. Hasil dari penelitian tindakan kelas ini menunjukkan bahwa terjadi peningkatan  pada kemampuan berbahasa siswa serta perubahan terhadap gaya belajar siswa. Kriteria Ketuntasan Minimal (KKM) pada pelajaran bahasa inggris adalah 70. Nilai siswa pada tahap awal sebesar 55.85, nilai rata – rata yang diperoleh siswa pada siklus pertama sebesar 66.13, dan 73.19 pada siklus kedua. Terdapat respon positif dari guru bahasa inggris terkait penerapan dan pelaksanaan penelitian ini serta pada perubahan gaya belajar siswa. Dengan kata lain dapat dikatakan bahwa penerapan active learning strategies dapat meningkatkan kemampuan berbahasa siswa serta perubahan signifikan pada gaya belajar siswa.